Watershed-scale modelling of the irrigated rice farming system at Muda, Malaysia, using the soil water assessment tool - Raffar, Nurfarhana; Zulkafli, Zed; Mok, Yiwen; Muharam, Farrah Melissa (Taylor & Francis, 2022)
Agricultural production in a highly managed watershed is challenging to capture in models due to its complexity and large hydrological, management, and crop data requirements. We evaluated hydro-crop simulation of Malaysia’s largest rice granary using the Soil Water Assessment Tool (SWAT). The 4515 km2 watershed is characterized by dams in the upper sub-watersheds that drain towards 1007 km2 of rice paddies. Monthly averaged streamflow simulation produced Nash-Sutcliffe efficiencies and coefficients of determination between 0.84 and 0.90 in both calibration and validation periods. Meanwhile, the normalized root mean square error and the percent bias for rice yield simulation in off and main seasons of rice planting were within ± 10%. Investigation of rice yield loss processes revealed a stronger control by solar radiation on crop growth processes compared to other hydroclimatic and environmental stresses. Our findings show that SWAT can reliably simulate streamflow and rice growth; however, it may not capture all yield loss processes.